Tracing the origin of the panda's thumb - Abella, Juan (2015)
We investigate the relative development of the carnivoran radial sesamoids to untangle the evolution of this iconic structure. In the pandas (both giant and red), this ‘false thumb’ is known to perform a grasping role during bamboo feeding in both the red and giant pandas. An original locomotor role has been inferred for ailurids, but this remains to be ascertained for ursids. A large sample of radial sesamoids of Indarctos arctoides from the Miocene of Batallones-3 (Spain) indicates that this early ailuropodine bear displayed a relatively hypertrophied radial sesamoid, with a configuration more similar to that of the red panda and other carnivorans than to that of giant pandas. This false thumb is the first evidence of this feature in the Ursidae, which can be linked to a more herbivorous diet. Moreover, in the two extant pandas, the false thumb should not be interpreted as an anatomical convergence, but as an exaptive convergence regarding its use during the bamboo feeding, which changes the evolutionary view of this singular structure.